Pengaruh Model Pembelajaran Problem Based Learning Berbantuan Media Audio Visual Terhadap Hasil Belajar Kognitif Siswa Pada Pembelajaran IPA Kelas IV SDN Gugus 12 Kota Bengkulu - Rahma Ginantia; Endang Widi Winarni; Abdul Muktadir (Universitas Bengkulu, 2023)
This study aims to determine the effect of Problem Based Learning model assisted by audio-visual media on students' cognitive learning outcomes in science subjects of grade IV Elementary School in Cluster 12 Bengkulu City. This type of research is quantitative research. The research method used is quasi-experimental design. With the design type